The economic cost of motorcycle accounts in Iloilo City. - Brodit, Vyel Marie C.; maghopoy, John Marti F. (2016.)
The increasing number of motorcycle accidents in the Philippines is a serious concern. Every accident involves costs, especially among the people involved. Using the Human Capital Approach, this study estimated the cost of motorcycle accidents in Iloilo City, focusing on the cost incurred by those involved in the accident, including the motorist, the passenger of the motorist, the driver of the other vehicle, and the pedestrian. Costs were also estimated according to the severity of the injury. Cost data were collected from 101 study participants who were involved in 92 separate motorcycle accidents in Iloilo City in 2015. The costs estimated include medical costs, productivity loss, property damages, accident settlement, other costs, and pain and suffering. Results show that the total cost of motorcycle accident was P82,507,768.25 or P26,377.16 per accident victim. The motorists incurred the largest cost at P36,897.51 per victim and the passengers incurred the least cost at P6,910.93 per victim. The medical expenses comprised 46 percent of the total cost, highlighting how motorcycle accidents pose a grave threat to health and to the household economy. Seriously injured victims incurred P170,594.98 per accident, while victims with minor injuries incurred P9,002.29 per accident. The study recommends for: 1) strict enforcement of road safety and traffic rules and regulation; 2) identification of areas where motorcycle accidents are common and studying the physical layout of the area that could have contributed to the accidents; 3) studying the factors contributing to motorcycle accidents; 4) including the cost of motorcycle accidents on society in future similar studies; and 5) the estimation of the optimal number of motorcycles on the road, which could guide the traffic program design.
Research Paper (Undergraduate, Bachelor of Science in Economics. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Motorcycle Accident